Best Practices in Physics-based Fault Rupture Models for Seismic Hazard Assessment of Nuclear Installations (Pageoph Topical Volumes,, 2018)
This volume collects several extended articles from the first workshop on Best Practices in Physics-based Fault Rupture Models for Seismic Hazard Assessment of Nuclear Installations (BestPSHANI). Held in 2015, the workshop was organized by the IAEA to disseminate the use of physics-based fault-rupture models for ground motion prediction in seismic hazard assessments (SHA). The book also presents a number of new contributions on topics ranging from the seismological aspects of earthquake cycle simulations for source scaling evaluation, seismic source characterization, source inversion and physics-based ground motion modeling to engineering applications of simulated ground motion for the analysis of seismic response of structures. Further, it includes papers describing current practices for assessing seismic hazard in terms of nuclear safety in low seismicity areas, and proposals for physics-based hazard assessment for critical structures near large earthquakes. The papers validate and verify the models by comparing synthetic results with observed data and empirical models. The book is a valuable resource for scientists, engineers, students and practitioners involved in all aspects of SHA.